MENINGKATKAN HASIL BELAJAR IPAS MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) SISWA KELAS IV SD NEGERI 14 LAKUDO - Sri Wulan Widianti; Manan Manan; Faslia Faslia (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the improvement of Science and Social Studies (IPAS) learning outcomes through the Contextual Teaching and Learning model among fourth-grade students at SD Negeri 14 Lakudo. This study employed Classroom Action Research conducted in two cycles, namely Cycle I and Cycle II. The research procedure followed the Kemmis and McTaggart model, which consists of four stages in each cycle: planning, acting, observing, and reflecting. The results showed that prior to the implementation of the through the Contextual Teaching and Learning model, students' classical learning outcomes were not yet optimal. Although the class average score reached 73.68, which fell into the good category, only 12 students achieved the Learning Objectives Completeness Criteria (KKTP), while the remaining 7 students were declared incomplete. After implementing the Contextual Teaching and Learning model, the learning outcomes of fourth-grade students at SD Negeri 14 Lakudo improved. This was evidenced by the increase in the class average score to 80 (good category), with the number of completed students rising to 18 and only 1 student remaining incomplete. The classical completeness rate in the final cycle reached 94.74%, meeting the completeness criteria. In conclusion, the implementation of the Contextual Teaching and Learning model has a positive and significant effect on the IPAS learning outcomes of fourth-grade students at SD Negeri 14 Lakudo.